From January to June: Birth seasonality across two centuries in a rural Polish community - Nenko Ilona; Briga Michael; Micek Agnieszka; Jasienska Grazyna (NATURE PORTFOLIO, 2025)
Seasonality of births is a worldwide phenomenon, but the mechanisms behind it remain insufficiently explored. Birth seasonality is likely to be driven by seasonal changes in women's fecundity (i.e. ability to conceive), which is strongly influenced by their energetic status. We tested whether birth seasonality is driven by high workload and/or low access to food using 200 years of birth data, from 1782 until 2004, in an agricultural rural Polish community. First, we analysed the time series of births and within-annual variance in births, a proxy for the extent of seasonality. Secondly, we tested the hypothesis that a high agricultural workload and/or low access to food decreases number of births. We found seasonality of births throughout more than 200 years of observation in an agricultural Polish population, with a dominant birth seasonality in January and February which gradually shifted towards June in the late twentieth century. The observed pattern does not support the hypothesis that birth seasonality resulted from women's energetic status. We discuss the possible reasons why our results do not support the tested hypothesis and some implications for our understanding of the birth seasonality.